Mapeamento de QTLs ligados à resistência parcial da soja à ferrugem asiática. - Santos, Karla Rodrigues Couto (2015)
The asian soybean rust is caused by Phakopsora pachyrhizi (Sydow & P. Syd.) fungus, is considered a very aggressive disease. Soybean plants are susceptible to asian rust at any developmental stage and, in many cases, yield losses may reach 80%. Cultivar development has been concentrated in using resistance (vertical) expressed by single major dominant or recessive genes, but there is a common understanding that this type of resistance may not be durable. Identifying promising crossing that can be used to develop genotypes with horizontal resistance (quantitative) will certainly help increase the longevity of the recommended cultivars. However, this type of resistance is subject to environmental variables that may difficult the selection. Consequently, this work has the objective to ranking crossings on the response to asian rust through their genetic estimates and predicted gains in order to identify the most promising crossings. The objective was also to identify QTLs associated with resistance to asian rust in soybeans in two different generations derived from the same crossing. Were ranked ten different crosses derived from seven cultivars in different combinations of these and the crossing of the cultivars IAC 100 (Partial Resistencia) and BRS Caiapônia (Susceptible) was the most promising. For the mapping of QTLs were used 87 F4 progeny derived from this cross, previously phenotyped at field. From the phenotyping data were prepared two DNA bulks that were used for the evaluation of 89 pairs of primer SSR (Simple Sequence Repeats). Of these 38 were polymorphic for the parents and the bulks. A linkage map for the F4 generation was obtained based on 29 SSR markers distributed in nine linkage groups, covering 285.9 cM genome. Six QTLs were mapped at four of these groups (C2, D2, L and N), two QTLs were detected for greater effect, accounting for 37.05% of the phenotypic variation for resistance to soybean rust. The linkage map constructed for the F7 generation was virtually identical to map the F4 generation, covering 266 cM. Four of the six QTLs mapped in the F4 generation were also identified in the F7 generation, showing stability for these genomic regions contributing to the horizontal resistance.